New insights into the pathogenesis of overactive bladder - Wróbel, Andrzej; Kulik-Rechberger, Beata; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
An xact knowledge of OAB pathophysiology facilitates the selection of the effective treatment. The proper functioning of the female urinary tract depends not only on very complex interactions between the cerebral cortex, spinal cord and anatomical components of the female lower urinary tract but also on the proper anatomical functioning of pelvic muscles, ligaments and fascias. Disturbances of the micturition reflex, morphological changes of nerves, smooth muscles and/or urothelium may contribute to the occurrence of OAB symptoms. In females, OAB symptoms may be caused by improper support of the bladder and urethra caused by anatomical damages of the pelvic floor.